ANALISIS STILISTIKA KUMPULAN PUISI ”DERU CAMPUR DEBU” KARYA CHARIL ANWAR - Suskandiati Suskandiati (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2019)
The purpose of this study was to describe (1) the diction, (2) prosody, and (3) the use of stylistic collection of poems